MULTILITERACY LEARNING IN NOMMENSEN THEATER FILMS IN BATAK (Lembaga Pengembangan Kinerja Dosen, 2022)
Multiliteracy learning in recent years has become very interesting because by studying two or more literacy materials we can see how they relate to other literacy materials. Especially when it comes to learning literature and language, the film Nommensen in Batak land is a theatrical film that has been accommodated and shown especially for the Batak community in North Sumatra and outside the Tapanuli area. The film is usually only made in memory of Nommensen. However, in this study, the film will be studied so that it can produce a multiliterate assessment contained in the film. The results of this study indicate that complete multiliteracy learning can be learned even in certain drama or cultural context films.